A DISCOURSE ANALYSIS OF PRESS RELEASES IN ENGLISH AND VIETNAMESE - Nguyễn Thị Phương Hà (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Press releases are short pieces of writing issued by companies or institutions to communicate newsworthy information to the journalist community and to the general public through newspaper reporting. Moreover, press releases are increasingly and directly by making available on corporate websites of the companies or organizations. While ostensibly informative, press releases also carry an implicitly self-promotional purpose, in so far as the information they contain comes from a source internal to the organization which is the object of the release itself. This paper contrastively analyzes the discourse features, i.e., discourse layout, lexical features, grammatical features and the cohesion in 100 English and 100 Vietnamese press releases. The findings reveal that, though in two languages, the informative and promotional function of press releases are interplayed with the format of logo-headline-lead-body copy-media contact. Lexically, the use of abbreviation and expressions denoting time, places, events, positive evaluation and expectation are employed in the elaboration of the press releases. The study also discusses some interesting and outstanding features of the corpus in terms of grammatical features with the utilization of different sentence types and voices. In terms of cohesion, the use of repetition is more popular in Vietnamese but reference is more common in English. Analysis of such discourse features in English and Vietnamese press releases will hopefully contribute to the study of the English language in general and the genre of press release in particular.